Reflexiones sobre la tesis doctoral “La raza antioqueña es única y no está degenerada” (2013)
ABSTRACT: In several countries, totalitarianism, fascism and national-socialism had racial topics as core policies. Other countries did not necessarily have a liberal thinking on this specific matter, and also approved discriminatory laws. In Latin America, eugenics had a great impact on public health policies during the first half of the 20th century, and gave rise to stigmatization of ill persons and of different races. Ninety years after its publication, a doctoral thesis on the race in Antioquia, Colombia, may still have validity.